Dynamique et croissance de l'Okoumé en zone côtière du Gabon - Fuhr, M.; Delegue, M.A.; Nasi, Robert; Minkoue, J.M. (Centre de Coopération Internationale en Recherche Agronomique pour le Développement, 1998)
Monitoring permanent plots established in pure natural stands of Okoumé (Aucoumea klaineana) in the coastal zone of Gabon from 1987 to 1997 allows reconstitution of the development pattern of such stands from their establishment to the so-called exploitable stage (around 60 years), and assessment of the impact of selective thinning from above (killing of standing trees) and traditional logging on the dynamics of such stands. Even-aged stands derive from recolonisation of agricultural clearings, and were identified from aerial photographs. They are distinguished from Okoumé-rich stands by the strong dominance of the species, which makes up at least 60% of the standing trees and 80% of the basal area in 20-60 year-old stands. Three successional stages are identified by the evolution of floristic composition through which pioneer species accompanying Okoumé in young stands are gradually replaced by species characteristic of the surrounding forest from the age of 5-10 years, young stands show a growth differential between Okoumé and all other species to the advantage of Okoumé, in both height increment (>1 m/year) and diameter increment (>1.5 m/year). At an age of about 15-20 years, the stands are vertically structured (overstorey and understorey). The evolution of their density is mainly due to natural mortality of understorey trees. Some equilibrium is reached at about 45 years, when some 100 dominant Okoumé trees per hectare make up 68% of the stands' total basal area (45 m2). The diameter growth of dominant Okoumé trees reaches a maximum between 5 and 15 years (>1.5 cm/year), and remains steady for at least 60 years (0.7 cm/year). Thinning carried out in 1989 removed an average of 36% of the basal area in young stands (15-30 years), and 21% in older stands (35-50 years). Over 80% of the volume removed was surplus overstorey Okoumé trees. Eight years later, both stands show a positive response. Stimulation of the diameter growth of individual Okoumé trees is quicker and marked in younger stands and the individual trees are smaller. However, the response of overstorey Okoumé trees is at present too limited to make up for loss of standing timber due to removal of trees, and appropriateness of the operation is being discussed. It is too soon to assess the impact of the logging operations on the growth of the stands, although preliminary results show that, despite an exceptionally high thinning intensity (15-20 trees/ha, representing a marketable volume of up to 100 m3/ha), a high number of overstorey and promising understorey trees are left standing. Post-logging regeneration, for the time being, only appears favourable to Okoumé in the most intensively logged plot.